Field studies on the Harlequin Duck in Iceland - Bengtson, Sven-Axel (Wildfowl, 1966)
A five-year study of a breeding colony of about 50 pairs of Harlequin Ducks on the River Lax near Myvatn, north-east Iceland, has added some numerical data on breeding behaviour, chronology and output to the meagre published information. The Harlequins return from the coats to the breeding river at the end of April and begin to lay from the middle of May. The interval between eggs is normally 2-4 days. Most eggs are laid in early June. The average clutch on the Lax is 5.5 eggs. Many eggs are collected (quite legally) by man. The Mink is probably the next most important predator. In recent years the ducks have increasingly nested on the banks of small remote streams instead of on islands in the river. Duckling survival is relatively high, with losses of about a third in the first week but few later. The males desert the females early, moving away from the nesting area, and play no parental role. The social and sexual behaviour in May, June and July is described. Territorial behaviour is most apparent in areas where pairs are scarce. Visual displays are probably less important than vocalizations. Feeding activity, described in detail, shows a diurnal rhythm, with greatest activity around 8-9 p.m. and 5 a.m. Harlequins are far more efficient divers in a fast-flowing river than other ducks. On the coast in winter they are much more gregarious and active than in summer.